Association Between Western and Mediterranean Dietary Patterns and Mammographic Density. Issue 3 (September 2016) - Castelló, Adela; Ascunce, Nieves; Salas-Trejo, Dolores; Vidal, Carmen; Sanchez-Contador, Carmen; Santamariña, Carmen; Pedraz-Pingarrón, Carmen; Moreno, Maria Pilar; Pérez-Gómez, Beatriz; Lope, Virginia; Aragonés, Nuria; Vioque, Jesús; et al.
Abstract : OBJECTIVE: To examine the association between two dietary patterns (Western and Mediterranean), previously linked to breast cancer risk, and mammographic density. METHODS: This cross-sectional study included 3, 584 women attending population-based breast cancer screening programs and recruited between October 7, 2007, and July 14, 2008 (participation rate 74.5%). Collected data included anthropometric measurements; demographic, obstetric, and gynecologic characteristics; family and personal health history; and diet in the preceding year. Mammographic density was blindly assessed by a single radiologist and classified into four categories: less than 10%, 10–25%, 25–50%, and greater than 50%. The association between adherence to either a Western or a Mediterranean dietary pattern and mammographic density was explored using multivariable ordinal logistic regression models with random center-specific intercepts. Models were adjusted for age, body mass index, parity, menopause, smoking, family history, hormonal treatment, and calorie and alcohol intake. Differences according to women's characteristics were tested including interaction terms. RESULTS: Women with a higher adherence to the Western dietary pattern were more likely to have high mammographic density (n=242 [27%]) than women with low adherence (n=169 [19%]) with a fully adjusted odds ratio (ORQ4vsQ1 ) of 1.25 (95% confidence interval [CI] 1.03–1.52). This association was confined to overweight–obese women (adjusted ORQ4vsQ1 [95% CI] 1.41 [1.13–1.76]). No association between Mediterranean dietary pattern and mammographic density was observed. CONCLUSION: The Western dietary pattern was associated with increased mammographic density among overweight–obese women. Our results might inform specific dietary recommendations for women with high mammographic density. Abstract : Supplemental Digital Content is Available in the Text.High adherence to the Western dietary pattern is associated with higher mammographic density; however, the Mediterranean dietary pattern is not.